Intrahepatic Cholestasis of Pregnancy： Biochemical Predictors of Adverse Perinatal Outcomes - 陈慧 周媛 邓东锐 郝海燕 党静 李静 (Journal of Huazhong University of Science and Technology. Medical sciences, 2013)
Summary： This study aimed to identify biochemical predictors of adverse perinatal outcomes in in- trahepatic cholestasis of pregnancy （ICP）. A total of 106 ICP cases were analyzed retrospectively by the combination of receiver operating characteristic curve and binary logistic regression analysis. ＂Adverse perinatal outcomes＂ included spontaneous preterm labor, meconium-staining of amniotic fluid, stillbirth and Apgar score ≤7 at 1 or 5 min. Total bile acid （TBA） [AUC=0.658, 95%CI （0.536, 0.781）, P=0.031] was a valuable predictor for adverse perinatal outcomes. The critical value of TBA above which adverse perinatal outcomes were observed was 40.15 μmol/L （Youden＇s index=0.3）. Binary multivariate logistic regression analysis revealed that the risk of adverse perinatal outcomes increased when TBA ≥40.15 /.tmol/L [OR=3.792, 95%CI （1.226, 11.727）, P=0.021]. It is concluded that the risk of adverse perinatal outcomes in ICP increases when maternal TBA ≥40.15 gmol/L.